Liver stiffness measurement using acoustic radiation force impulse elastography in overweight and obese patients. Issue 4 (30th June 2016) - Attia, D.; Bantel, H.; Lenzen, H.; Manns, M. P.; Gebel, M. J.; Potthoff, A.
Summary: Background: Obesity and overweight are global health problems. Aim: To evaluate the diagnostic accuracy of liver stiffness measurement (LSM) using acoustic radiation force impulse (ARFI) elastography in overweight and obese patients for staging liver fibrosis. Methods: Ninety‐seven patients (mean age: 50 years, 50% male) with body mass index (BMI) ≥25 kg/m 2 (mean BMI: 31 kg/m 2 ) were prospectively enrolled. All patients underwent ARFI elastography and liver biopsy. In 87/97 patients, transient elastography (TE) was performed (M‐ and XL‐probes). Patients were divided into two groups respectively: overweight: BMI <30 kg/m 2 ( n = 61); and obese: BMI ≥30 kg/m 2 ( n = 26). Results: Acoustic radiation force impulse elastography correlated with liver fibrosis in overweight ( r = 0.84, P < 0.0001) and obese patients ( r = 0.85, P < 0.0001), while no correlation was observed with steatosis, steatohepatitis and BMI. Area under the curve detecting liver cirrhosis for ARFI and TE were 0.97 in overweight and 0.94 and 0.92 in obese patients. In both groups, the failure rate was lower for ARFI than TE. ARFI of liver segment 8 showed a lower discordance than TE in both groups (overweight: 3% vs. 12%, P = 0.002; obese: 8% vs. 27%, P = 0.034). Steatosis and steatohepatitis were neither predictors of discordance nor of performance in LSM by ARFI or TE in both groups. Conclusions: In overweight and obese patients, acoustic radiation force impulse can diagnose liver cirrhosis and significant fibrosis with high diagnostic accuracy. Liver stiffness measurement using the XL‐probe reduces the influence of BMI, steatosis and steatohepatitis. The failure and discordance rates were lower for acoustic radiation force impulse than transient elastography in both patients groups.